1984
DOI: 10.1002/bbpc.198400048
|View full text |Cite
|
Sign up to set email alerts
|

Sonolysis of Chloroform

Abstract: Radiation Chemistry / Radicals / SonolysisChloroform is decomposed by irradiation with ultrasonic waves to yield a large number of products. The major products are various unsaturated compounds. Decomposition occurs only in the presence of a monoatomic-or diatomic gas. Free radicals and carbenes are postulated as intermediates of sonolysis which can only be scavenged by volatile additives such as O 2 or c-hexene. In the presence of 10070 c-hexene, the rate of sonolysis of chloroform is increased and various ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The thermoelectric properties of the SWCNT buckypapers can be discussed with the chemical modification of SWCNTs through the chloride radicals. It has been reported that chlorine radicals generated from chlorinated solvents could react with the sidewalls of SWCNTs. Because chlorine is an electron-withdrawing group, the hole carrier concentration of SWCNTs might increase by using CF. The origin of the thermoelectric properties affected by the solvent is still uncertain.…”
Section: Resultsmentioning
confidence: 99%
“…The thermoelectric properties of the SWCNT buckypapers can be discussed with the chemical modification of SWCNTs through the chloride radicals. It has been reported that chlorine radicals generated from chlorinated solvents could react with the sidewalls of SWCNTs. Because chlorine is an electron-withdrawing group, the hole carrier concentration of SWCNTs might increase by using CF. The origin of the thermoelectric properties affected by the solvent is still uncertain.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the relative behavior of these intermediates, depending on the specific nature of the solute, suggests that somewhat different mechanisms are operative. In the case of CHCl 3 sonolysis, the following mechanism is probable: In an alternative pathway, the pyrolytic decomposition of CHCl 3 may proceed via a molecular elimination reaction to form dichlorocarbene Dichlorocarbenes may then self-react to give C 2 Cl 4 as observed by Hua and Hoffmann (3)…”
Section: Resultsmentioning
confidence: 99%
“…A variety of radical species were identified in chloroform and other organic solvents. For example, the sonication of chloroform generates a variety of radicals as shown in Reaction (13) [17].…”
Section: Sonochemistrymentioning
confidence: 99%